Midichloria mitochondrii stimulates the sylvatic cycle of Borrelia burgdorferi (sensu lato) in Ixodes ricinus and contributes to Lyme disease risk - Clara F. Köhler; Maya L. Holding; Manoj Fonville; Ron P. Dirks; Hans J. Jansen; Sara Moutailler; Aurélie Heckmann; Jens Zarka; Erik Matthysen; Hein Sprong; Aleksandra I. Krawczyk (Current Research in Parasitology and Vector-Borne Diseases)
Sex and symbionts of arthropod vectors are potential modulators of infection with vector-borne pathogens. Here, we investigated the involvement of sex and presence of the bacterial symbiont Midichloria mitochondrii in immature stages of Ixodes ricinus ticks on the acquisition and abundance of the tick-borne spirochete Borrelia burgdorferi (sensu lato). There was no difference in the infection rate of M. mitochondrii between male and female larvae. The infection with M. mitochondrii but not tick sex increased the acquisition of B. burgdorferi (s.l.) by I. ricinus larvae feeding on naturally infected birds. The infection with B. burgdorferi (s.l.) in questing nymphs was positively associated with M. mitochondrii, but not with their sex. The infection rates of M. mitochondrii in field-collected ticks showed substantial spatial variation. In our field study, we observed that locations exhibiting higher M. mitochondrii prevalence in nymphs also have significantly higher infection rates with B. burgdorferi (s.l.). Thus, the M. mitochondrii symbiont appears to enhance the ability of immature I. ricinus ticks to acquire and/or maintain B. burgdorferi (s.l.) in nature and is therefore an additional factor that contributes to the spatial variation in Lyme disease risk.